Sustainable Science Through a Case Study of Sample Preparation Using 3D Printed Tools. - Whitmore, Lawrence (European Journal of Sustainable Development, 2023)
The combination of cloud-based resources, user-friendly cloud-based design applications and 3D printing (3DP) is making possible a new sustainable paradigm in scientific research. Tools and components can be self-made by downloading model designs, optimizing those designs for individual experiments and printing locally. Together with the use of materials for 3DP filaments derived from renewable resources and recycling of old printed structures, science labs and institutes can significantly reduce their carbon footprint to meet their Sustainable Development Goals. This new sustainable paradigm is evaluated through a case study of sample preparation - a fundamental aspect of materials science. For high quality investigation of material microstructures, even to the atomic scale, sample preparation is critical. A range of 3DP plastic tools for preparing samples has been developed. The design and fabrication of a 3DP vibrational polishing machine and a 3DP dimpling machine are described along with test results from microstructural analyses of brass and silicon that show the high-quality scientific studies possible using these low-CO2e tools. Keywords: 3D printing, sustainable development, sustainability mindset, carbon footprint, materials science, sample preparation.